Fostering commitment as a tool in environmental education to alleviate littering in rural schools - Maunatlala, Phoko Martha (University of the Witwatersrand, Johannesburg, 2024)
Littering is a major and leading cause of environmental degradation, and a widespread form of waste is plastic. Plastics are useful material which present numerous advantages in the daily lives of people; however, they are a problem for society and the environment. Plastic can have dire implications for both plant and animal species inside and outside water. Its presence can be seen in soil, water and air, and is covered in school subjects such as life sciences, agricultural sciences, geography, life orientation and economics. Despite the recognition of plastic pollution as an environmental issue, littering of plastic is still pervasive in some rural schools in South Africa. Learners do litter, as educators do not put outdoor activities of environmental education into practice. To break down the barriers to practising environmental education in outdoor activities, a behaviour change is necessary. This study applied qualitative, quantitative, observation and interview methods to investigate barriers to anti-littering before and after intervention in two rural schools. Litter education was also employed using photographs of littering in different locations of the two schools. The pictures of the impact of plastic litter on animals living on land and in the water, as well as solutions were taught to both learners and educators. Litter education was coupled with a school environmental policy drafted by the educators of both schools to instruct learners on how to properly dispose of waste. A behaviour changes commitment pledge tool was introduced in both schools as an intervention measure, which encouraged learners to participate in the circular economy, which also encouraged them to treat their environment responsibly. Hence, they pledged to protect animals from being fed plastic. Dustbins and other anti-litter measures such as recycling, reusing and reducing plastic were used to prevent plastic pollution from affecting birds and animals. At school A, learners were introduced to a public and written commitment pledge. At school B, they were introduced to a private and written commitment pledge as an intervention tool. The learners were observed, engaged in sorting, disposed of waste appropriately and practiced the circular economy for four weeks, including follow-ups. The researcher observed that learners who wrote public pledges sorted waste more than those who made written and private pledges.
A research report Submitted in fulfillment of the requirements for a Master of Education, In the Faculty of Humanities , Wits School of Education, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Fostering commitment; rural schools; SDG-4: Quality education; SDG-15: Life on land